Carbon anhydrase IX specific immune responses in patients with metastatic renal cell carcinoma potentially cured by interleukin-2 based immunotherapy. (August 2013) - Rasmussen, Susanne; Donskov, Frede; Pedersen, Johannes W.; Wandall, Hans H.; Buus, Søren; Harndahl, Mikkel; Braendstrup, Peter; Claesson, Mogens H.; Pedersen, Anders Elm
Abstract The majority of clear-cell renal cell carcinomas (ccRCC) show high and homogeneous expression levels of the tumor associated antigen (TAA) carbonic anhydrase IX (CAIX), and treatment with interleukin-2 (IL-2) based immunotherapy can lead to cure in patients with metastatic renal cell carcinoma (mRCC). However, the involvement of CAIX specific CD8+ T cells and/or NK cells in the tumor eradication is unknown. We investigated T cell and antibody reactivity against overlapping 15-mer CAIX-peptides as well as HLA haplotype frequency and NK cell cytotoxicity in 11 patients with no evidence of disease (NED) following treatment with IL-2 based immunotherapy, and thus potentially cured. Immune reactivity in these patients was compared with samples from patients with dramatic tumor response obtained immediately at the cessation of therapy, samples from patients that experienced progressive disease during treatment and samples from healthy controls. We observed more focused but only weak and not consistent CAIX specific T-cells in the late observation and early observation response groups compared with the healthy control group. An increased frequency of the class II alleles HLA-DRB4 01:01, HLA-DPB 01:01 and HLA-DPB 03:01 was noted in the NED patients. In contrast, NK cytotoxicity was low even in the late observation response group as compared with controls. In particular, a HLA-B*40:01 restricted CD8+ T cell response recognizing the CAIX- derived peptide SEEEGSLKL was identified. This may have interest in future cancer vaccines, but more studies are needed to elucidate the immunological mechanisms of action in potentially cured patients treated with an immunotherapeutic agent.